Wide area robust centralized PSO-based specified structure H∞ power system damping controller design considering uncertainties in time delay and system parameters - Ngamroo, Issarachai (My University, 2013)
It is well known that the time delay due to the wide area phasor measurement may cause a malfunction of wide area centralized control of power system damping controller (PSDC) and system instability eventually. Nevertheless, the uncertainties due to time delay and system parameters have never been considered in the previous researches of PSDC design. To tackle this problem, a wide area robust centralized particle swarm optimization (PSO)-based specified structure H∞ PSDC design taking uncertainties due to communication delay and system parameters into account is proposed in this paper. Without explicit mathematic equations, the inverse input multiplicative model is applied to represent the unstructured uncertainties. The structure of PSDC is the practical 2nd order lead/lag compensator. To automatically tune the control parameters, the optimization based on an enhancement of damping effect and robust stability margin is achieved by PSO. To evaluate the proposed design technique, two examples of robust centralized PSDC, i.e., power system stabilizer and thyristor control series capacitor are demonstrated in a two-area four-machine interconnected power system,. Simulation study confirm that the proposed robust centralized PSDC is much superior to the conventional centralized PSDC in terms of stabilizing effect and robustness against uncertainties due to time delay and system parameters. © 2013 ICIC International.
Keywords: H∞ control; Particle swarm optimization; Phasor measurement unit; Power system stability; System uncertainties; Time delay; Wide area monitoring system